Women's Participation in Productive Business Development through the Modeling of Baitul MÄl Wa at-TamwÄ«l in Palembang - Junaidi, Heri; Lidyah, Rika; Agustina, Ria; Rima Putri Pratama, Chici (El-Barka, 2023)
This study is motivated by the fact that women's efforts to participate in developing productive businesses do not yet have the right model so that their activities appear to be just a side job. Meanwhile, women's productivity in the micro economy in the new normal era will have a positive impact on strengthening the home economy, as well as restoring the activities of micro businesses that have gone bankrupt as a result of the pandemic. The presence of Baitul Maal Wa Tamwil with the financing assistance model and financial management literacy of Baitul Maal Wa Tamwil makes the administration process easier and more synergistic. The data used for this article comes from qualitative research, using interviews and relevant literature. The respondents of this research are Palembang gender activist academics, BMT administrators, business actors in areas with a majority of women who carry out productive business development in Palembang. interviews using the snowball sampling method. The research results showed that women's participation in productive business development after a long period in the domestic sphere due to the COVID-19 pandemic has become more varied and provides additional benefits for the family economy. The presence of BMT helps women's productive businesses, providing administrative convenience for obtaining financing and changing the home management model to family management established by BMT. This research then found that after a long period of time women were in the domestic sphere due to the regulations during the Covid-19 Pandemic, their product activity patterns changed to profitable home businesses. Furthermore, the management model used by BMT is more accepted and supported by Palembang women who are developing their businesses.